Community Perceptions On Tourism Impacts: A Case Of University Students In Malaysia - Hamimi, Omar (1996)
The purpose of this study is to evaluate Malaysia’s university students’ perceptions of the tourism industry in Malaysia, particularly focusing on the differences in perceptions between the Muslim and non-Muslim students. The rapid development of tourism in the recent years, in line with the country’s healthy long-term economic prospects and the government’s commitment to tourism, resulted in the increase of employment opportunity in the tourism industry in Malaysia. However, there is a great concern for the participation of the Muslim population in tourism related jobs. Tourism has always being associated with alcohol and general permissiveness by the Muslims and the two Factors are prohibited by their religion. The findings of the analysis, therefore, reveal some important assumptions that can be useful for future references. The study proves that there are broadly similar views among the students from both Muslim and non-Muslim respondents. In fact,a very high percentage of the answers stresses the benefits of tourism. In general terms, the majority welcome tourism for economic reasons, and see it as a positive force. However, a distinct minority see some problems arising from tourism. Having said that, it is interesting to note that there is a difference in perceptions between the liberal and orthodox Muslims themselves. Several recommendations are made particularly concerning local community participation in developing an area, and the emphasis on higher education for tourist related areas. All of these will be discussed at length in the next chapters.